An Adaptive Conjoint Analysis of Freight Service Alternatives: Evaluating the Maritime Alternative - Angela S. Bergantino; Simona Bolis (European Regional Science Association (ERSA), 2003)
The growing interest towards a re-balancing of freight traffic over the different modes, has brought renewed focus on the "Motorways of the sea" as they have been defined by the EU Commission in the recently issued White paper (2001). These could constitute a valid alternative to land transport over medium-long distance, favouring, at the same time, a greater integration among different modes. However, the great potential of this alternative - which is increasingly capturing the interest of policymakers - should be evaluated also in the light of the level of competitiveness nowadays required by the operators. The latter, in fact, need a flexible transport system capable of adapting to the modern system of production and completely integrated within the logistics networks (both existing and under construction). Furthermore, in order to effectively promote the use of this alternative, it is necessary to undertake a number of initiatives directed mainly at reducing the bottlenecks currently present within the ports and in the links between ports and their interland. In determining the necessary investments in intermodal sea-land infrastructures it is essential to evaluate the dimension and the extent of the potential re-orientation of traffic flows towards maritime transport which would yield insight on the appropriate/optimal dimension of such investments. In order to achieve this, it would be essential to have a set of information not only on the current movements but also on their potential reallocation. An estimation of the latter cannot be achieved without an in-depth analysis of shippers behaviour. However, while in the last year a number of documents have been put forward on the great opportunities offered by the development of the "Motorways of the sea" in re-directing freight flows, there is a lack of any empirical analysis on the determinants of such choice by operators. In other words, a lot has been done in analysing supply while very little in analysing demand. In this work we aim to identify the value that the user assigns to the specific transport alternative and the factors - related to both the mode and the specific organisation of the companies - that exert a significant influence on the choice of the shipper. These elements represent a necessary prerequisite for any previsions. The methodology used falls within the definition of conjoint Analysis. We will measure the trade-offs users of freight transport services make in choosing between alternative modes. We will also use the result to predict their choices with regards to alternatives which, at the moment might not be present, but which might be placed on the market. The assumption we make, following the approach of Bolis and Maggi (1999) and Fowkes and Tweddle (1996), is that the transport service can be ?broken down? into its component attributes. As it is well known, conjoint analysis allows to determine the value that individuals place on any product as equivalent to the sum of the utility they derive from all the attributes making up a product. In particular, given the successful applications to land transport, we use "Adaptive Stated Preferences" (ASP) techniques adjusted in order to carry out the analysis of freight transport demand in the maritime context. We aim to evaluate the preferences of operators in terms of service attributes of sea transport. Given the purposes of this study, for the moment we focus the empirical application on a specific geographical context. In particular, we analyse the preferences of operators localised in the north-west regions of Italy with respect to the possibility of accessing a maritime ro-ro service from the ports of Genoa or La Spezia. The analysis is carried out in two phases: a postal survey and a subsequent direct interview. The latter is done creating a ?transport experiment? and recording the behaviour and the choices of the interviewed. Following this approach, we obtain an accurate estimation of operators' willingness to pay for the specific service characteristics (hard output) and we induce them to reveal the rank of their preferences for a set of potential new services (soft output). In the first part of the paper we give details of the specific transport options we are considering and we describe the project carried out, in the second part we illustrate the methodology used the and the necessary modification we have had to carry out in order to implement the study in a maritime context. In the third part we discuss the data collection process and we carry out a preliminary data analysis, while, in the fourth section, we present the results of the econometric model (logit model) used to analyse the data and we give some interpretation. Finally, in the last section, we present some concluding remarks.
Keywords: 330